2018
DOI: 10.1021/acsami.8b15210
|View full text |Cite
|
Sign up to set email alerts
|

From Alloy to Oxide: Capturing the Early Stages of Oxidation on Ni–Cr(100) Alloys

Abstract: The interaction of oxygen with Ni−Cr(100) alloy surfaces is studied using scanning tunneling microscopy (STM) and spectroscopy (STS) to observe the initial steps of oxidation and formation of the alloy−oxide interface. The progression of oxidation was observed for Ni(100) and Ni−Cr(100) thin films including Ni−8 wt % Cr(100) and Ni−12 wt % Cr(100), which were grown on MgO(100) in situ. These surfaces were exposed to between 1 and 150 L O 2 at 500 °C, and additional annealing steps were performed at 500 and 600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 54 publications
(136 reference statements)
1
46
0
Order By: Relevance
“…3. This was in agreement with studies on the early stages of oxidation on binary alloys where it was shown that the first oxides formed were nickel, nucleated as islands distributed across the surface of the specimen [4][5][6][7]. It has also been shown that a metastable chromium-oxygen phase formed on the surface of binary alloys, surrounding the NiO islands [5][6][7][8][9].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…3. This was in agreement with studies on the early stages of oxidation on binary alloys where it was shown that the first oxides formed were nickel, nucleated as islands distributed across the surface of the specimen [4][5][6][7]. It has also been shown that a metastable chromium-oxygen phase formed on the surface of binary alloys, surrounding the NiO islands [5][6][7][8][9].…”
Section: Discussionsupporting
confidence: 90%
“…These processes have been studied for some pure metals and simple alloy systems using exacting experimentation techniques; e.g. [1][2][3][4][5][6][7][8][9]. These studies involved monitoring the changes occurring to clean metallic surfaces when exposed to oxidising environments, using a number of high spatial resolution techniques.…”
Section: N Warnken Amentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, a comprehensive understanding of oxidation mechanisms is necessary to evaluate applicability of a material in a desired environment. Characterising one or more oxides formed during the initial stages of oxidation is a significant challenge because oxidation of alloying elements is simultaneous with the nucleation and growth of metastable phases 10,11 . Further, the composition across buried oxide/metal interfaces can also change, often heterogeneously, depending on the crystallographic orientation of the base metal grains below 6 , requiring a spatially resolved analysis of such changes.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the experimental difficulties connected to the timescale of the early oxidation of clean alloy surfaces. [30,31] In addition, with the increase of the main steam parameters, the corrosion of superheater and reheater becomes more serious. [2] To mitigate the overall corrosion of the power plant, water chemistry-related species, such as oxygen, have been added to feedwater.…”
Section: Introductionmentioning
confidence: 99%